2018
DOI: 10.1364/optica.5.001315
|View full text |Cite|
|
Sign up to set email alerts
|

Strong circular dichroism for the HE11 mode in twisted single-ring hollow-core photonic crystal fiber

Abstract: Received XX Month XXXX; revised XX Month, XXXX; accepted XX Month XXXX; posted XX Month XXXX (Doc. ID XXXXX); published XX Month XXXX We report a series of experimental, analytical and numerical studies demonstrating strong circular dichroism in helically twisted hollow-core single-ring photonic crystal fiber (SR-PCF), formed by spinning the preform during fiber drawing. In the SR-PCFs studied, the hollow core is surrounded by a single ring of non-touching capillaries. Coupling between these capillaries result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(27 citation statements)
references
References 28 publications
0
27
0
Order By: Relevance
“…Twisting the fibre ring also allows these resonant frequrncies to be tailored. Our results could be also be useful to researchers working on twisted solid-core and hollow-core photonic crystal fibres [13,42]…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Twisting the fibre ring also allows these resonant frequrncies to be tailored. Our results could be also be useful to researchers working on twisted solid-core and hollow-core photonic crystal fibres [13,42]…”
Section: Discussionmentioning
confidence: 79%
“…[12]. Twisted ring arrays of fibres and other helical waveguides have been developed to explore new ways to manipulate optical AM in a discrete fashion [13,14]. Optical AM may be exploited for a plethora of applications including astronomical observation [15][16][17], classical [18,19] and quantum [20,21] communication, optomechanics [22,23] and microscopy [24].…”
Section: Introductionmentioning
confidence: 99%
“…This has been explored both in freespace [2] and in optical fibers with circularly symmetric cylindrical or annular cores [3]. In recent years it has been shown that optical fibers with N-fold rotationally symmetric structures (such as most photonic crystal fibers -PCFs) support helical Bloch modes (HBMs) that consist of superpositions of Bessel beams with azimuthal order A (m) = A (0) + mN where m is an integer [4]. These may be viewed as HBM harmonics that are coupled together by Bragg scattering in the azimuthally periodic fiber structure.…”
Section: Introductionmentioning
confidence: 99%
“…Twisted PCFs are also circularly birefringent [5], making them of interest in Faraday-effect current sensing when preservation of circular polarization state is highly desirable [6]. They can also provide strong circular dichroism [4], allow generation of broad-band circularly polarized supercontinuum light [7] and even permit guidance of light in the absence of any structural core [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Numerically obtained relations between n′ cl and dominating orbital angular momentum L D = J D −σ cannot be accurately described using analytical formulas derived for the modes guided in similar but simpler structures, like thin cylindrical layers [35] or cylindrical arrays of weakly coupling waveguides [36,37]. However, similarly as in case of annular modes guided in thin cylindrical layers, the effective index of the cladding modes in microstructured fiber n cl decreases for greater L and increases for greater ρ, regardless of λ.…”
mentioning
confidence: 99%